2021
DOI: 10.1038/s41418-021-00845-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel CDC25A/DYRK2 regulatory switch modulates cell cycle and survival

Abstract: The cell division cycle 25A (CDC25A) phosphatase is a key regulator of cell cycle progression that acts on the phosphorylation status of Cyclin–Cyclin-dependent kinase complexes, with an emergent role in the DNA damage response and cell survival control. The regulation of CDC25A activity and its protein level is essential to control the cell cycle and maintain genomic integrity. Here we describe a novel ubiquitin/proteasome-mediated pathway negatively regulating CDC25A stability, dependent on its phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…9 ). Given the working venue model that nucleus CDC25A functions in cell cycle progression while cytoplasmic CDC25A is prone to degradation [ 28 , 29 ], we envision that CDC25A exon 6 skipping generated from SRSF10 not only restrains UPS-dependent protein degradation due to the absence of two ubiquitin sites but also accelerates its nuclear aggravation to enhance its cell cycle phosphatase activity.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…9 ). Given the working venue model that nucleus CDC25A functions in cell cycle progression while cytoplasmic CDC25A is prone to degradation [ 28 , 29 ], we envision that CDC25A exon 6 skipping generated from SRSF10 not only restrains UPS-dependent protein degradation due to the absence of two ubiquitin sites but also accelerates its nuclear aggravation to enhance its cell cycle phosphatase activity.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…TRIM33 and BACH1 could regulate the activation of activation of Wnt/β-catenin ( Jiang et al, 2015 ; Li et al, 2022 ), and L. reuteri protect the intestinal mucosal barrier integrity by moderately modulating the Wnt/β-catenin pathway to avoid overactivation ( Wu et al, 2020 ). DYRK2 , RORA and other genes are also involved in the regulation of cell cycle ( Lara-Chica et al, 2022 ), apoptosis ( Li et al, 2022 ) and other activities. The above studies also fully confirmed that these candidate genes identified in this study may be potential regulatory molecules of L. reuteri to protect host cells against E. coli F18ac.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CDC25A is a key factor in regulating the cell cycle and is regulated by eca-miR-200a. Mutual feedback regulation between CDC25A and DYRK2 has important implications for genotoxic stress pathways, apoptosis and cell cycle regulation [ 43 ]. In epididymal tissue, four genes were demonstrated with miRNA roles, including BMP5 , GCNT1 , FGF7 and THSD4 .…”
Section: Discussionmentioning
confidence: 99%